Realism in Immune Ecology Studies: Artificial Diet Enhances a Caterpillar's Immune Defense but Does Not Mask the Effects of a Plastic Immune Strategy - Costantin, Eduardo C.; Viol, Daniel L.; Del Puppo, Nathalia P.; Elliot, Simon L. (Frontiers in Insect Science, 2022)
The immune system is considered a functional trait in life-history theory and its modulation is predicted to be costly and highly dependent on the host's nutrition. Therefore, the nutritional status of an individual has a great impact on an animal's immune ecology. Herbivorous insects are commonly used as model organisms in eco-immunology studies and the use of an artificial diet is the predominant rearing procedure to test them. However, this diet differs from what herbivores experience in nature and it is unclear to what degree this distinction might impact on the relevance of these studies for the real world. Here, we compared plant-based vs. artificial diet in a set of three experiments to investigate the interaction of both diets with a plastic immune strategy known as Density-Dependent Prophylaxis (DDP). We used as a model organism the velvetbean caterpillar Anticarsia gemmatalis, which is known to adjust its immune defense in line with the DDP hypothesis. Our main results showed that larvae fed with artificial diet had 20.5% more hemocytes circulating in the hemolymph and died 20% more slowly when infected with an obligate (viral) pathogen. Crucially, however, we did not find any indication of fitness costs related to DDP. The use of artificial diet did not interact with that of DDP except in the case of host survival after infection, where the DDP effect was only observable in this diet. Our findings suggest the use of an artificial diet does not mask resource allocation conflicts between immune investment and fitness related traits, but to some extent it might lead to an overestimation of immune parameters and host survival time after infection. We believe that this is the first study to compare an artificial diet and a host plant covering all these aspects: immune parameters, life-history traits, and host survival after infection. Here we provide evidence that, besides the quantitative effects in immune parameters and host survival time, the use of artificial diet interacts only marginally with a density-dependent immune response. This provides support for the use of artificial diets in eco-immunology studies with insects.